Oral health problem among pregnant mothers: age and attitude do matter - Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; Abllah, Zurainie (2017)
Introduction: Oral health care during pregnancy is greatly important as it is crucial to the health and well-being to both pregnant mother and baby. Studies showed that mothers with oral health problem have greater risk of prematurity and low birth weight babies. This study aimed to measure the associated factors of oral health problem among pregnant mothers. Materials and Methods: This cross sectional study was conducted among purposely selected 296 pregnant mothers aged 18-45 years from the biggest district in Pahang State, Malaysia. This 18 months study used validated self-administered questionnaire which was asking on socio-demographic characteristics, and knowledge, attitude and practice on oral health. Oral health status was assessed by dentists using Community Periodontal Index of Treatment Need (DFMT index). Descriptive analysis used to describe respondents background and multinomial logistic regression used to examine the associations. Results: Majority of the respondents (89.9%) were among young mothers (35 years), Malay (91.9%), mean gestation of two, and from low socioeconomic status (59.5%). Of the 296 respondents, 111 (48.1%) had low experience with dental caries, 57 (24.7%) had moderate experience, and 63 (24.3%) had high experience with dental caries. Older age had higher risk to experience dental caries and those who had good attitude were protected, p=0.018 and p=0.023 respectively. Conclusion(s): Age and attitude were significant factors associated to oral health problem among pregnant mothers. Thus, health promotion and good attitude should be instilled from younger age.